2004
DOI: 10.1038/nn1241
|View full text |Cite
|
Sign up to set email alerts
|

Extrastriate body area in human occipital cortex responds to the performance of motor actions

Abstract: A region in human lateral occipital cortex (the 'extrastriate body area' or EBA) has been implicated in the perception of body parts. Here we report functional magnetic resonance imaging (fMRI) evidence that the EBA is strongly modulated by limb (arm, foot) movements to a visual target stimulus, even in the absence of visual feedback from the movement. Therefore, the EBA responds not only during the perception of other people's body parts, but also during goal-directed movements of the observer's body parts. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
385
5
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(432 citation statements)
references
References 43 publications
41
385
5
1
Order By: Relevance
“…The recognition of a stationary body of other people involves the extrastriate body area (EBA), and recent research suggests that one's own body movements (e.g., of hand and foot) can also involve the EBA [Astafiev et al, 2004;Jeannerod, 2004]; More importantly, human motions such as body, gaze, and hand movements involve the superior temporal sulcus (STS). This is most often identified at the right hemisphere (all studies reported in Table I or 100%) and less so at the left hemisphere (55%).…”
Section: Identifying the Social Othermentioning
confidence: 99%
“…The recognition of a stationary body of other people involves the extrastriate body area (EBA), and recent research suggests that one's own body movements (e.g., of hand and foot) can also involve the EBA [Astafiev et al, 2004;Jeannerod, 2004]; More importantly, human motions such as body, gaze, and hand movements involve the superior temporal sulcus (STS). This is most often identified at the right hemisphere (all studies reported in Table I or 100%) and less so at the left hemisphere (55%).…”
Section: Identifying the Social Othermentioning
confidence: 99%
“…a chair, a spoon) (Downing et al, 2001, Moro et al, 2008, Urgesi et al, 2004Peeen and Downing 2005). However many recent studies suggest EBA relation with more cognitive functions and frontal sensorimotor regions (Astafiev et al, 2004;Helmich et al, 2007;David et al, 2007). Recent studies have shown functional connectivity of EBA with higher cortical areas such as the PMC and posterior parietal cortex (PPC) during different cognitive tasks, such as mental hand rotation (Helmich et al, 2007) or self-other attribution (David et al, 2007).…”
Section: Two-route Model Of Body Processingmentioning
confidence: 99%
“…Thus, the patients showed high activity in the right angular gyrus when they experienced being the agent of their actions, whereas this activation in healthy controls is only seen when agency is allocated to another person. The role of this brain region in self and bodily processing is further supported by functional imaging studies in healthy individuals (Astafiev, Stanley, Shulman, & Corbetta, 2004;Bonda, Petrides, Frey, & Evans, 1995;Calvert, Campbell, & Brammer, 2000;Lobel, Kleine, Bihan, Leroy-Willig, & Berthoz, 1998;Uddin, Kaplan, Molnar-Szakacs, Zaidel, & Iacoboni, 2005) and by patients with focal brain lesions (e.g., Apperly, Samson, Chiavarino, & Humphreys, 2004;Scepkowski & Cronin-Golomb, 2003;Semenza, 1988).…”
mentioning
confidence: 91%